Skrb za pitno vodo - Cerar, Sonja (Geografija Slovenije, 2014)
Safeguarding Drinking WaterLjubljana's water resources lie in the immediate vicinity of built-up urban areas or even below them. For decades, they have been safeguarded as water-protection areas, which are specified by implementing regulations. However, formal protection through regulations is insufficient if the goal is to manage these sources in a sustainable manner. One of the most important goals of sustainable management is maintaining suitable provision of fresh drinking water without using any technological procedures to